2020
DOI: 10.1111/andr.12779
|View full text |Cite
|
Sign up to set email alerts
|

Significance of piezo‐type mechanosensitive ion channel component 2 in premature ejaculation: An animal study

Abstract: Background Penile hypersensitivity is one of the main pathological mechanisms of premature ejaculation. However, little is known about the neurophysiological mechanism of penile peripheral nerve sensitization. Piezo Type Mechanosensitive Ion Channel Component 2 (PIEZO2), was recently identified as a mechanically sensitive channel. Objectives This study explored the possible neural mechanisms of PIEZO2 action in the mechanisms of premature ejaculation using molecular biology and electrophysiology approaches. Ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…It is noteworthy that the role of Piezo2 channels has been demonstrated in premature ejaculation rats, with the involvement of inward currents [18], although we suggest that the mechanism is related to peripheral nerve sensitization and not to TAD-like lesions. Accordingly, premature ejaculation related to mechanical hypersensitivity involves significantly increased Piezo2 in the penis head and in the dorsal root ganglion (DRG) [18] without mechano-energetic lesions.…”
Section: Cellular Mechanism Of the Critical Primary Injurymentioning
confidence: 52%
See 2 more Smart Citations
“…It is noteworthy that the role of Piezo2 channels has been demonstrated in premature ejaculation rats, with the involvement of inward currents [18], although we suggest that the mechanism is related to peripheral nerve sensitization and not to TAD-like lesions. Accordingly, premature ejaculation related to mechanical hypersensitivity involves significantly increased Piezo2 in the penis head and in the dorsal root ganglion (DRG) [18] without mechano-energetic lesions.…”
Section: Cellular Mechanism Of the Critical Primary Injurymentioning
confidence: 52%
“…It is noteworthy that the role of Piezo2 channels has been demonstrated in premature ejaculation rats, with the involvement of inward currents [18], although we suggest that the mechanism is related to peripheral nerve sensitization and not to TAD-like lesions. Accordingly, premature ejaculation related to mechanical hypersensitivity involves significantly increased Piezo2 in the penis head and in the dorsal root ganglion (DRG) [18] without mechano-energetic lesions. However, in the case of POIS, and underlying DOMS, it is theorized that the Piezo2 channels of the proprioceptive axon terminals of the muscle spindle in the bulbospongiosus and ischiocavernosus muscles suffer an acute stress induced mechano-energetic lesion.…”
Section: Cellular Mechanism Of the Critical Primary Injurymentioning
confidence: 52%
See 1 more Smart Citation
“…This may be a result of the Piezo2 channels of the proprioceptive axon terminals of the bulbospongiosus and ischiocavernosus muscle spindles experiencing acute stress-induced mechanoenergetic lesion, 12 as Piezo2 is involved in the pathogenesis of PE. 26 …”
Section: Discussionmentioning
confidence: 99%
“…To the best of our knowledge, the expression of PIEZO2 in preputial mechanoreceptors has not been investigated. However, Chen et al, ( 2020 ) studied the role of PIEZO2 in the mechanism underlying premature ejaculation in rats and reported that PIEZO2 expression was significantly increased in the penile head and dorsal root ganglia of these rats.…”
Section: Introductionmentioning
confidence: 99%